2019
DOI: 10.1029/2018jb016917
|View full text |Cite
|
Sign up to set email alerts
|

Strain Localization and Weakening Processes in Viscously Deforming Rocks: Numerical Modeling Based on Laboratory Torsion Experiments

Abstract: Localization processes in the viscous lower crust generate ductile shear zones over a broad range of scales affecting long-term lithosphere deformation and the mechanical response of faults during the seismic cycle. Here we use centimeter-scale numerical models in order to gain detailed insight into the processes involved in strain localization and rheological weakening in viscously deforming rocks. Our 2-D Cartesian models are benchmarked to high-temperature and high-pressure torsion experiments on Carrara ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Our predictions of the depth of the BDT agree well with observations of volcanic events (Ágústsdóttir et al., 2019; Sigmundsson et al., 2015) and natural (Blanck et al., 2019) and drilling‐induced seismicity (Friðleifsson et al., 2018) in Iceland, where basalt is extensively present as the main lithology. The model results are in good agreement with experimental evidence (Adelinet et al., 2013; Döhmann et al., 2019; Meyer et al., 2019; Nardini et al., 2018; Violay et al., 2012, 2017), in situ observations (Ágústsdóttir et al., 2019; Friðleifsson et al., 2014, 2017), and theoretical arguments (Carcione et al., 2018; Horii & Nemat‐Nasser, 1986; Parisio et al., 2019). The approach taken can be extended to study other lithologies such as carbonatic basements in which the depth of the BDT would be shallower (Parisio et al., 2019), or above‐average geothermal gradient around local temperature anomalies, such as shallow‐depth magma pockets (Elders et al., 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our predictions of the depth of the BDT agree well with observations of volcanic events (Ágústsdóttir et al., 2019; Sigmundsson et al., 2015) and natural (Blanck et al., 2019) and drilling‐induced seismicity (Friðleifsson et al., 2018) in Iceland, where basalt is extensively present as the main lithology. The model results are in good agreement with experimental evidence (Adelinet et al., 2013; Döhmann et al., 2019; Meyer et al., 2019; Nardini et al., 2018; Violay et al., 2012, 2017), in situ observations (Ágústsdóttir et al., 2019; Friðleifsson et al., 2014, 2017), and theoretical arguments (Carcione et al., 2018; Horii & Nemat‐Nasser, 1986; Parisio et al., 2019). The approach taken can be extended to study other lithologies such as carbonatic basements in which the depth of the BDT would be shallower (Parisio et al., 2019), or above‐average geothermal gradient around local temperature anomalies, such as shallow‐depth magma pockets (Elders et al., 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Since inclusions, weak spots, and heterogeneities are likely to be ubiquitous in the Earth's crust, we believe that this assumption well represents the actual conditions. Laboratory experiments have also confirmed that a single inclusion could trigger localized shear strain under pressure and temperature conditions that would instead lead to homogeneous strain patterns in homogeneous samples (Nardini et al, 2018) and large deformation creep models have shown the necessity of including strain-softening in order to agree with the observations (Döhmann et al, 2019). Nevertheless, localization is possible in nonassociated plasticity and is triggered by the appearance of singularities in the acoustic tensor (Grassl & Jirásek, 2006;Rudnicki & Rice, 1975), themselves associated with acceleration waves (Lemaitre et al, 2009).…”
Section: 1029/2020jb020539mentioning
confidence: 98%
“…Note that the employed random number generator srand can yield variable patterns for different library configurations; hence, individual model details are currently not reproducible on other computers, only the overall ensemble behavior. To facilitate localization, we use softening laws for (i) brittle layers (e.g., Brune, 2014; Jourdon et al., 2021; Persaud et al., 2017; Petersen & Schiffer, 2016; Salazar‐Mora et al., 2018) and (ii) ductile parts of the crust (e.g., Döhmann et al., 2019; Gerbi et al., 2010; Pérez‐Gussinyé et al., 2020) (Table 1). Brittle softening is implemented as a linear decrease of the friction coefficient by up to 90% between accumulated strain values of 0–0.5.…”
Section: Numerical Model Setupmentioning
confidence: 99%
“…However, the physical processes within shear bands, which control their width, are often considered to be beyond the scope of current geodynamic models. Hence, for sake of simplicity, strain localization is often induced by a priori-defined strain-softening functions (Buck & Lavier, 2001;Buiter et al, 2006;Döhmann et al, 2019;Huismans & Beaumont, 2002;Lavier et al, 1999), which are meant to take into account the role of complex thermo-hydro-chemico-mechanical interactions within faults in a phenomenological sense.…”
Section: Introductionmentioning
confidence: 99%